Top secret! [videorecording (Blu-Ray)] - Kilmer, Val, 1959-; Gutteridge, Lucy, 1956-; Cushing, Peter, 1913-1994 (Paramount Home Entertainment, 2022)
Nick Rivers is America's hottest rock idol-turned-super-spy. Nick must race against time to save the world from destruction from the ultimate superweapon the Polaris Mine. Packed with action, gags, and random musical interludes, it manages to do for war epics and Elvis flicks what AIRPLANE! did for disaster movies.